Qualitative Assessment of Entrepreneurial Activities of Malaysian Private Tahfiz Institutions (PTIs) - Anas, Norazmi; Saleh, Muhammad Hafiz; Yaacob, Zuriani; Mohd Taharin, Mohd Aariffin; Rokhman , Wahibur (Environment-Behaviour Proceedings Journal, 2021)
PTIs are encouraged to participate in entrepreneurial activities appropriate for their area and ability. Thus, this qualitative case study where a semi-structured interview with the selected Malaysian Private Tahfiz Institutions (PTIs) was conducted to identify entrepreneurial activities to pay operational and management costs, to analyze the obstacles, limitations, problems faced, and to assess the balance of entrepreneurial activities in educational governance of these religious, educational institutions. The findings demonstrated that involving PTIs in entrepreneurship can cover 40 to 50 percent of total operating costs. Keywords: Qualitative Assessment; Entrepreneurial Activities; Malaysian Private Tahfiz Institutions (PTIs); Malaysia eISSN: 2398-4287Â© 2021. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians/Africans/Arabians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v6i18.3056